The Role of Legal Certainty Theory in Realizing Corporate Accountability in Indonesian National Standardization - Septyandi Terok, Doni Fanni; Suhartati, Suhartati (Universitas Islam Sultan Agung, 2023)
Indonesian national standardization (SNI) is a set of technical requirements established by the National Standardization Council (DSN) to ensure the quality of goods, services, and processes. The rapid development of technology as it is today makes it easy for various imported goods to enter Indonesia at low prices. To guarantee quality, it is necessary to implement SNI, which is supported by Article 8 Paragraph (1) Letter a of Law Number 8 of 1999 concerning Consumer Protection which stipulates that business actors are prohibited from producing and/or trading goods that do not meet or are not in accordance with Indonesian National Standards (SNI). The purpose of this research is to analyze the role of legal certainty theory in realizing corporate liability in Indonesian national standardization (SNI). The research method used is qualitative with a descriptive approach, and data collection is done through literature study. The data collected was then analyzed through the stages of reduction, presentation, and conclusion drawing. The results showed that the theory of legal certainty has an important role in realizing corporate liability in the Indonesian national standardization (SNI). Legal certainty in Indonesian national standardization (SNI) can be realized through the application of clear, transparent, and consistent laws and regulations, as well as the application of strict and consistent sanctions.